EFFECTS OF INVENTORY MANAGEMENT ON BUSINESS PERFORMANCE OF ELECTRONIC COMPANIES IN MOGADISHU, SOMALIA. - MOHAMUD, HUSSEIN ABUKAR; OMAR, DR NAGIB (IJRDO - Journal of Business Management, 2016)
The study will be examining the role of inventory management and cost reduction in organization in Electronic Companies. Nowadays, we usually think of stocks being held by organizations to allow efficient and continuous operations. Managers are aware of the vital roles inventory plays in the activities of organizations. The research design of this study will be quantitative design. In addition, clear definition of the details of the quantitative makes the desired statistical analyses possible, and usually improves the usefulness of the results. The Electronic Companies are Target Population .Research instruments can be helpful tools to your research study,. Because the information needed can be easily and quickly gathered from the respondents, and it can target respondents in widely dispersed locations, in questionnaire development, Research instrument used in the Data collection is questionnaire to measure the variable(s), characteristic(s), or information of interest, often a behavioral or psychological characteristic. Data processing is essential for a scientific study and for ensuring that we have all relevant data for making contemplated comparisons and analysis. the study recommends that the electronic companies should not only undertake Inventory planning in order to improve operation and sustain failing businesses but also improve their competitiveness and financial performance